The relationship between patient safety culture with patient satisfaction and hospital performance in Shafa Hospital of Kerman in 2020 - Parya Jangipour Afshar; Bahram Jabarzadeh Karbasi; Mahmood Nekoei Moghadam (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Hospitals are a significant part of the health system, so their performance is always measured based on some factors such as patient satisfaction and their safety level. AIM: The present study was aimed to examine the relationship between patient safety culture with patient satisfaction and hospital performance. MATERIALS AND METHODS: This descriptive-analytical, cross-sectional study was performed on 240 patients, 240 staff and 20 hospital managers in Shafa hospital of Kerman, Iran, in 2020. To collect data, the patient safety culture, the patient satisfaction, and the hospital performance questionnaires were used. The data were analyzed by SPSS and PLS software; to measure the research model, structural equation models and confirmatory factor analysis were used. RESULTS: The variable "patient satisfaction" and its components had a high mean, with the component "the treating physician" having the highest mean. The variables "patient safety culture and hospital performance" had a medium mean. There was a significant positive relationship between patient safety culture-hospital performance, patient safety culture-patient satisfaction, and patient satisfaction-hospital performance. CONCLUSION: The patient satisfaction level was appropriate in the studied center, and a positive and significant relationship was found between patient safety culture and patient satisfaction and hospital performance.